PERSEPSI GAYA KEPEMIMPINAN DAN KOMITMEN ORGANISASI - GUMGUM GUMELAR F.R; AYU FITRIA NUROHMI (Journal of Research and Measurement in Psychology, 2017)
The purpose of this research is to test if there are any influence between transformational leadership style and transactional leadership style to the organization commitment from the college executive’s faculty council member at State University of Jakarta. The research’s subject insist of 94 college executive’s faculty council member at State University of Jakarta, whose chosen using Proportionate Stratified Random Sampling technic. On data processing process used pure score from Rasch modeling. The measuring tool which used to organizational commitment is ocq which constructed by Meyer and Allen. Meanwhile, for transformational leadership style and transactional leadership style using MLQ form 6s measuring tool which constructed by Bass and Avolio. On data processing process used double regression modeling. The result is transformational leadership style influencing organizational commitment significantly with influence amount (Adjusted R Square) 0.277 (22.7%). While transactional leadership style influencing organizational commitment insignificantly with influence amount (Adjusted R Square) 0.139 (13.9%).